Influence of teachers’ motivation on students’ performance in KCSE in public secondary schools in Kinangop sub county Nyandarua county, Kenya - Wambugu, Daniel Kihara (My University, 2018)
Work place motivation is an important factor that inspires workers in any organization to pursue their goals and perform their duties effectively. However, lack of motivation among public secondary school teachers in Kinangop Sub-County has negatively affected quality of teaching and learning, leading to poor performance in national examinations. The purpose of this study was to investigate the influence of teachers’ motivation on students’ performance in KCSE in Kinagop sub county, Nyandarua County. The objectives were, determining the influence of teachers’ empowerment, appreciation, collaboration and selfefficacy on students’ performance in KCSE in public secondary schools in Kinagop SubCounty. The study was guided by Maslow’s theory of motivation, and Herzerburg’s two factor theory. Triangulation design was used, which utilized both quantitative and qualitative analyses at the same time. The target population comprised 28 headteachers and 310 teachers totaling to 338 respondents. Slovin’s formula was used to select a sample of 184 participants. Stratified random sampling was employed to create 8 zones based on the 8 administrative wards within the sub-County. Using simple random sampling, 2 headteachers from each ward were sampled and 168 teachers from each ward. Questionnaires were used to gather quantitative data from teachers and interview guides from headteachers. Piloting was carried out in two secondary schools in the neighboring Kipipiri sub-County, where 2 headteachers and 5 teachers were involved. Validity was determined by involving experts in the department of Educational Administration and Curriculum Studies. Reliability was established through test retest technique. Reliability index was assessed by use of Pearson’s Product Moment Correlation Coefficient Method. A coefficient of r=0.65 was achieved indicating a high internal reliability. Credibility was ascertained through data triangulation through input of multiple analyses. Dependability was achieved through detailed reporting of procedures of data collection. Qualitative data analysis was done thematically in narrative forms, while quantitative data was analyzed descriptively using frequencies and percentages, means and standard deviation, while results were presented using tables and figures. The study found that various elements of teachers’ motivation, such as empowerment, appreciation, collaboration and self-efficacy enhance the quality of teaching and learning, leading to improved students’ performance in KCSE. The study established that teachers’ empowerment creates positive change, since teachers gain mastery of curriculum and acquire better skills. It was found that teachers’ appreciation through rewards and incentives for performance enhances work commitment, increases engagement with students, leading to improved academic performance. It was however established that only a few teachers collaborate through lesson planning. The study recommended that teachers need more opportunities of professional development, such as continuous learning, skill acquisition in areas of communication, leadership and organization, that it is important for Teachers Service Commission to establish performance based reward system.
Keywords: Motivation; Secondary; Teachers